Wirausaha Ramah Lingkungan Berbasis Produksi Ferro Sulfat dari Limbah Besi - Sunardi Sunardi; Muhammad Dzakwan; Sugiyarmasto Sugiyarmasto; Argoto Mahayana; Sumardiyono Sumardiyono (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
Indiscriminate disposal of iron waste into waters or the environment will be harmful to human health and the environment. In this regard, there must be an understanding of how to properly utilize iron waste so that it can provide economic value along with an understanding of environmentally friendly technology-based entrepreneurship. This community service activity has the aim of providing understanding for students of SMK Tunas Nusantara Department of Industrial Chemistry by utilizing iron waste into ferrous sulfate. The training provided includes: environmentally friendly entrepreneurship, the dangers of iron waste, how to make ferrous sulfate from iron waste and how to package it. The methods used in the training are: improvement and understanding through lectures, questions and answers, demonstrations, and practice. During the training, the Tunas Nusantara Vocational School students participated in the training activities well and enthusiastically. The results of the training resulted in SMK students having knowledge about environmentally friendly entrepreneurship which was shown to be able to make ferrous sulfate from iron waste and continue to work on it as an alternative to environmentally friendly technology-based entrepreneurship.